Review of technologies for low-quality solid fuel gasification. (May 2019) - Lutyński, A; Lutyński, M
Abstract: The article discusses World's current status of surface coal and other resources gasification technology. Examples of existing and planned gasification plants efficiencies up to the year 2022 along with the use of syngas for chemical resources production and distribution of plants are given. The SGT (SES Gasification Technology) gasification technology where produced syngas is used for energy production is described.